EFFECT OF HAMSTRING-EMPHASIZED RESISTANCE TRAINING ON HAMSTRING: QUADRICEPS STRENGTH RATIOS - HOLCOMB, WILLIAM R.; RUBLEY, MACK D.; LEE, HEATHER J.; GUADAGNOLI, MARK A. (Journal of strength and conditioning research, 2007)
A decreased hamstring:quadriceps (H:Q) ratio may put the hamstrings and anterior cruciate ligament (ACL) at increased risk of injury. Therefore, the purpose of this study was to evaluate H:Q ratios of 12 female National Collegiate Athletic Association soccer players, and to test the effects of a 6-week strength training program on these ratios. Each subject completed 2 practice sessions before a pretest. Subjects then completed 6 weeks of strength training that included the addition of 2 hamstring specific exercises, followed by a posttest. Peak torque during concentric and eccentric actions for both hamstrings and quadriceps was measured with an isokinetic dynamometer. Each muscle action was tested at 3 angular velocities in the following orderconcentric 240, 180, and 60°·s and eccentric 60, 180, and 240°·s. The H:Q strength ratio was evaluated using concentric muscle actions (concentric hamstringsconcentric quadriceps). This method is commonly used and is thus called the conventional ratio. Because concentric actions do not occur simultaneously in opposing muscles, a more functional assessment compares eccentric hamstring actions to concentric quadriceps actions. This functional ratio was also analyzed. Mean conventional and functional H:Q ratio data were analyzed using separate analysis of variance procedures with repeated measures on all factors (2 [Test] × 2 [Leg] × 3 [Angular Velocity]). The results revealed a significant main effect for factor (F test) with the functional ratio (p < 0.05) but not for the conventional ratio. The mean functional ratio increased from 0.96 ± 0.09 in pretest to 1.08 ± 0.11 in posttest. These results suggest that 6 weeks of strength training that emphasizes hamstrings is sufficient to significantly increase the functional ratio. The functional ratio after training exceeded 1.0, which is specifically recommended for prevention of ACL injuries.